Integrative Analysis of Pharmacokinetic and Metabolomic Profiles for Predicting Metabolic Phenotype and Drug Exposure Caused by Sotorasib in Rats - Du, Ping; Liu, Lihong; Hu, Ting; An, Zhuoling (Frontiers in Oncology, 2022)
Sotorasib is a novel targeted inhibitor of KRAS (G12C), which has shown exciting tumor suppressing effect not only for single targeted agent but also for combination with immune-checkpoint inhibitors. However, no any integrative analysis of pharmacokinetics (PK) and pharmacometabolomics (PM) of Sotorasib was reported until now. In present study, a sensitive and robust high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) method was firstly developed and fully validated for quantitating Sotorasib in rat plasma. After one-step protein precipitation, Sotorasib and internal standard (carbamazepine) were separated on Waters XBrige C18 column (50 mm×2.1, 3.5 μm) and analyzed in electrospray ionization positive ion mode. The optimized method was fully validated according to guidance, and was successfully applied for a PK study of Sotorasib at dose of 10 mg/kg. Besides, a longitudinal and transversal PM was employed and correlated with PK using partial least squares model and Pearson analysis. With the help of multivariate statistical analysis, the selected 6 (AUC model) and 9 metabolites (Cmax model) completely distinguish the high- and low-group after Sotorasib treatment, which indicate that these potential biomarkers can predict drug exposure or toxicity. The results of this study will shed light on how Sotorasib disturbed the metabolic profiles and the relationship between PK and PM, as well as offer meaningful references for precision therapy in patients with KRAS (G12C) mutation.